A map of Terengganu - Awang Goneng (Singapore : Monsoon Books, 2011)
The sequel to Malaysian bestseller Growing Up in Trenaggnu looks at the terrain of Trengganu, the landmarks that are still standing and those that have fallen to rubble, the winds that bring chill and change to the inhabitants of his coastal town, and the people who walked the streets and breathed air laced with the aroma of dried shrimps
Keywords: Goneng, Awang -- Chilhood and youth; Terengganu -- Biography; Terengganu -- Social conditions -- 20th century